2024
DOI: 10.15277/bjd.2024.435
|View full text |Cite
|
Sign up to set email alerts
|

fresh start with high hopes: a qualitative evaluation of experiences of the Total Diet Replacement phase of the NHS Low Calorie Diet Programme pilot

Catherine Homer,
Karina Kinsella,
Kevin James Drew
et al.

Abstract: Background: The National Health Service (NHS) Low Calorie Diet (LCD) programme in England aims to support people with type 2 diabetes (T2DM) to lose weight, improve glycaemic parameters and potentially achieve diabetes remission. The programme pilot launched in 2020 using three different delivery models: one-to-one, group and digital via an App. Service users begin the programme with 12 weeks of Total Diet Replacement (TDR). This study aims to understand the experience of this TDR phase from the service user p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…22 Findings from the studies detailed within this paper are reported elsewhere in this issue. [23][24][25][26][27]…”
Section: The Nhs Lcd Programmementioning
confidence: 99%
“…22 Findings from the studies detailed within this paper are reported elsewhere in this issue. [23][24][25][26][27]…”
Section: The Nhs Lcd Programmementioning
confidence: 99%
“…18 A desire for peer support was also reported by some participants, which aligned with findings from participant interviews at 12 weeks (end of the TDR phase). 19 The importance of peer support was highlighted in a recent meta-analysis which demonstrated greater post-intervention weight loss and lower BMI in individuals who received peer support compared to usual care. 20 Ufholz also demonstrated the positive participant perception of peer support, which may be particularly effective in supporting vulnerable at-risk populations and may improve long-term adherence.…”
Section: Original Researchmentioning
confidence: 99%